A new allele, HLA‐A*03:275N. (5th April 2017) - Battarra, M.; Condello, R.; Galluccio, T.; Stellitano, C.; Andreani, M.
Abstract : The novel allele HLA‐A*03:275N differs from HLA‐A*03:01:01:01 by 1 nucleotide substitutions in exon 2